ISLAMIC RELIGIOUS EDUCATION, STUDENT ACTIVITY AND INTOLERANCE IN STATE SENIOR HIGH SCHOOLS IN YOGYAKARTA - Aniek Handajani; Noorhaidi Hasan; Tabita Christiani (Aqlam: Journal of Islam and Plurality, 2019)
Abstract Several studies show the presence of intolerance and Islamist attitudes strengthened among teachers and students. However, studies on ‘radicalization’ process among teenagers at school are still limited. We address the issue by analyzing intolerance tendency, examining the religious education at school and revealing the shift of intolerance tendency among students. By conducting mixed methods research in three public schools, this study uncovers seven factors that cause the shift of intolerance tendency: First, stakeholders formulate school vision which endorses religious tolerance in public schools. Second, the school policies that support pluralism and tolerance towards other differences in the school environment. Third, government and school leaders conduct training to provide teachers with knowledge to counter radical teachings. Fourth, teachers integrate local wisdoms in their teaching materials. Fifth, the student activities, particularly Islamic religious activities, which accommodate pluralism and endorse tolerance towards different religions, ethnics and cultures. Sixth, the supervision of books and materials from the internet that contain radical doctrines by parents and teachers. Seventh, involving Islamic mainstream organizations in countering radical ideology and mitigating intolerance in public schools. Regarding Islamist movements at schools, we suggest that religious education, if properly formulated can be used to counter Islamist radicalism at school effectively.Key words: Intolerance, Islamist movements, Radical ideology, Religious, Education AbstrakBeberapa studi menunjukkan adanya intoleransi dan sikap Islamis yang menguat di kalangan guru dan siswa. Akan tetapi penelitian mengenai proses 'radikalisasi' di kalangan remaja di sekolah masih terbatas. Kami menyikapi masalah ini dengan menganalisa kecenderungan intoleransi dan meneliti pelaksanaan pendidikan agama di sekolah. Dengan memakai metode gabungan di tiga sekolah umum, studi ini mengungkap adanya penurunan kecenderungan intoleransi pada tahun 2017 - 2018. Penelitian ini mengungkap enam faktor yang mempengaruhi penurunan intoleransi agama di kalangan siswa. Pertama, para pemangku kepentingan merumuskan visi sekolah yang mendukung toleransi beragama. Kedua, kebijakan sekolah yang mendukung pluralisme dan toleransi terhadap agama lain di sekolah.  Ketiga, pemerintah dan pimpinan sekolah mengadakan pelatihan bagi para guru untuk memberikan pengetahuan dalam rangka mengatasi paham radikal. Keempat, guru mengintegrasikan kearifan lokal dalam bahan ajar mereka. Kelima, kegiatan siswa terutama kegiatan Kerohanian Islam, yang mengakomodasi keberagaman dan mendukung toleransi terhadap berbagai agama, etnis, dan budaya. Keenam, pengawasan buku dan bahan dari internet yang mengandung doktrin radikal oleh orang tua dan guru. Ketujuh, melibatkan organisasi mainstream Islam dalam melawan ideologi radikal dan memitigasi intoleransi di sekolah umum. Sedangkan mengenai gerakan Islamis di sekolah, kami berpendapat bahwa pendidikan agama jika diformulasikan dengan benar dapat dipakai untuk melawan radikalisme di sekolah secara efektif.Kata kunci: Intoleransi, Gerakan Islamis, Ideologi radikal, Pendidikan Agama